Upaya Meningkatkan Keterampilan Shotting Bola Basket Melalui Metode Demonstrasi di Kelas VIII A SMP Negeri 2 Arut Selatan Tahun Pelajaran 2019/2020: Efforts to Improve Basketball Shooting Skills Through Demonstration Methods in Class VIII A of SMP Negeri 2 Arut Selatan for the 2019/2020 Academic Year - Sujatmiko, Agus (Anterior Jurnal, 2022)
Teaching techniques and basic movement skills in sports to a large number of students requires a method that can cover the activity of all students in participating in the learning process. Also included in teaching basketball techniques, students must be active as a whole in receiving the material, especially if the material is in the form of mastering the basic skills and techniques of one sport. The teacher who plays the role of a researcher here wants to improve students’ skills in practicing basketball shooting through the demonstration method. In the pre-cycle, an observation score of 48 was obtained, meaning that the students’ basketball shooting skills were not good. Furthermore, researchers feel it is so important to carry out research using demonstration methods. In the first cycle, the observation results showed a score of 111, meaning that the students’ basketball shooting skills were quite good. However, to make it more conducive for students’ basketball shooting skills, the researchers wanted to carry out cycle II. In the second cycle, the observation results showed a score of 145, meaning that the students’ basketball shooting skills were very good. In the student observation activity, the teacher assessed that students can make one-handed shots (One-hand Set Shot), students can do free throws (Free Throw), students can shoot while jumping (Jump shot), students can do hook shots ( Hook Shot) and students can do a Lay Up.